(untitled) (Bangladesh Veterinarian, 2016)
This study determined bacterial quality of chicken rolls sold in a fast food restaurant at Bangladesh Agricultural University (BAU) campus. Fifteen chicken rolls (ten premicrowaved and five post-microwaved) were collected. Samples were inoculated into selective media, Eosin Methylene Blue (EMB) agar, Salmonella Shigella (SS) agar, Thiosulphate Citrate Bile Salts Sucrose (TCBS) agar and Mannitol Salt (MS) agar. The total viable count (TVC) and total Staphylococcal count (TSC) of pre-microwaved samples were 4.4 log CFU/g and 4.2 log CFU/g, respectively. In post-microwaved samples, the TVC and TSC were 2.7 log CFU/g and 2.6 log CFU/g, respectively. Microwave treatment significantly reduced the TVC and TSC in the chicken rolls (P<0.05). Bacteria were recovered only from samples inoculated onto MS agar. Colonies on MS agar were characteristics of Staphylococcus spp, confirmed by sugar fermentation, catalase and coagulase tests and polymerase chain reaction (PCR) assay. This study recorded coagulase negative staphylococcus (CNS) resistant to three antibiotics, ampicillin, cephalexin and vancomycin. It is suggested that chicken rolls sold in the fast food restaurant contaminated with resistant CNS might pose a public health hazard. Bangl. vet. 2015. Vol. 32, No. 1, 13-18